Heterojunction solar cell, preparation method thereof and photovoltaic module
By depositing an oxygen-doped amorphous silicon layer and a doped amorphous silicon layer on the front and back of the heterojunction solar cell, the damage problem of UV radiation to the battery is solved, and the UV resistance and photoelectric conversion efficiency of the battery are improved.
Patent Information
- Application Number
- CN202411788376.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
When heterojunction solar cells are used in ultraviolet (UV) environments for a long time, UV radiation will damage the packaging materials and the thin film layer inside the battery, reducing the photoelectric conversion efficiency and life.
By depositing an oxygen-doped amorphous silicon layer and a doped amorphous silicon layer on the front and/or the back of the battery, the hydrogen atom concentration and the doping concentration of phosphorus or boron of the doped amorphous silicon layer are adjusted to enhance resistance to UV radiation.
The quality and uniformity of the amorphous silicon thin film are improved, the passivation effect is enhanced, the damage to the internal structure of the battery is reduced, and the efficiency of the battery's absorption and utilization of ultraviolet rays is improved.
Smart Images

Figure BDA0005174686350000151 
Figure BDA0005174686350000161 
Figure HDA0005174686370000011
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solar cells, and in particular to a heterojunction solar cell sheet and a preparation method thereof, and a photovoltaic module. Background Art
[0002] Heterojunction solar cell (HJT) is a high-efficiency crystalline silicon solar cell. It uses crystalline silicon (c-Si) as the substrate material and introduces amorphous silicon on its surface or interface to form a heterojunction to improve the photoelectric conversion efficiency and stability of the cell. Moreover, due to its unique double-sided structure and the passivation effect of the intrinsic layer, heterojunction cells have many advantages such as high conversion efficiency, no light-induced degradation, good temperature characteristics, and a short manufacturing process. Therefore, heterojunction cells have great market potential.
[0003] However, in practical applications, heterojunction cells are exposed to ultraviolet light for a long time. UV radiation not only affects the packaging materials of the cell, but may also damage the thin film layer inside the cell, thereby reducing the photoelectric conversion efficiency and life. The long-term reliability of heterojunction cells in ultraviolet (UV) environments has become an urgent problem to be solved. Summary of the invention
[0004] The present invention aims at the above problems, makes up for the deficiencies of the prior art, and provides a heterojunction solar cell and a preparation method and assembly thereof to solve the problems arising from the above background technology.
[0005] The first aspect of the present invention provides a heterojunction solar cell, comprising: a silicon substrate; a front passivation layer, a front doping layer, a front transparent conductive layer, and a front metal electrode are arranged on the front side of the silicon substrate from the inside to the outside; a back side passivation layer, a back side doping layer, a back side transparent conductive layer, and a back side metal electrode are arranged on the back side of the silicon substrate from the inside to the outside;
[0006] Wherein, the front passivation layer and / or the back passivation layer comprises an oxygen-doped amorphous silicon layer;
[0007] The front doping layer and / or the back doping layer includes a doped amorphous silicon layer, and the hydrogen atom concentration of the doped amorphous silicon layer is 4.5×10 19 / cm 3 ~5.5×10 19 / cm 3 (For example: 4.5×10 19 / cm 3 5.0×10 19 / cm 3 , 5.5×10 19 / cm 3 The doping concentration of phosphorus or boron is 5.0×1017 / cm 3 / ~5.0×10 19 / cm 3 (For example: 5.0×10 17 / cm 3 , 1.5×10 18 / cm 3 , 3.5×10 18 / cm 3 , 4.5×10 18 / cm 3 , 5.5×10 18 / cm 3 , 6.5×10 18 / cm 3 , 7.5×10 18 / cm 3 , 8.5×10 18 / cm 3 , 9.5×10 18 / cm 3 , 1.5×10 19 / cm 3 , 2.5×10 19 / cm 3 , 3.5×10 19 / cm 3 , 4.5×10 19 / cm 3 5.0×10 19 / cm 3 etc., not specifically limited here).
[0008] The front passivation layer and the back passivation layer of the present invention are one or more thin films used to provide field passivation effect, reduce carrier recombination, and improve battery efficiency; the front doping layer and the back doping layer are one or more thin films that change the conductive properties of the material by introducing atoms or ions; the front transparent conductive layer and the back transparent conductive layer are one or more thin films used to transmit photons and current.
[0009] The present invention deposits an oxygen-doped amorphous silicon layer and a doped amorphous silicon layer on the front and / or back of the battery, and the hydrogen atom concentration of the doped amorphous silicon layer is 4.5×10 19 / cm 3 ~5.5×10 19 / cm 3 , the doping concentration of phosphorus or boron is 5.0×10 17 / cm 3 ~5.0×10 19 / cm 3, enhancing its resistance to UV radiation, specifically: depositing an oxygen-doped amorphous silicon layer, which helps to optimize the deposition environment, reduce the formation of impurities and defects, thereby improving the quality and uniformity of amorphous silicon films and enhancing the passivation effect; depositing a doped amorphous silicon layer, the hydrogen atom concentration of the doped amorphous silicon layer is 4.5×10 19 / cm 3 ~5.5×10 19 / cm 3 Within this range, the silicon-hydrogen bond is relatively stable and not prone to breakage, thus reducing the damage of ultraviolet rays to the internal structure of the battery. When the hydrogen atom concentration is less than 4.5×10 19 / cm 3 When the concentration of hydrogen atoms is greater than 5.5×10 19 / cm 3 When the amorphous silicon structure is not obtained; the absorption characteristics of the doped amorphous silicon layer to light are different from those of microcrystalline silicon. By adjusting the doping concentration of the doped amorphous silicon layer, the doping concentration of phosphorus or boron in the doped amorphous silicon layer is 5.0×10 17 / cm 3 ~5.0×10 19 / cm 3 The spectral response characteristics of the cell can be optimized to better match the ultraviolet band in the solar spectrum, which helps to improve the absorption and utilization efficiency of the cell for ultraviolet rays. The interface between the doped amorphous silicon layer and the transparent conductive layer is smoother, reducing the reflection and transmission loss of light at the interface, which allows more ultraviolet rays to enter the cell and be effectively absorbed and converted. When the doping concentration of phosphorus or boron in the doped amorphous silicon layer is less than 5.0×10 17 / cm 3 When the doping concentration of phosphorus or boron in the amorphous silicon layer is greater than 5.0×10 19 / cm 3 When the structure changes, the composite effect is enhanced and the risk of leakage increases.
[0010] More preferably, the doping concentration of phosphorus or boron is 1.5×10 18 / cm 3 ~3.0×10 18 / cm 3 (For example: 1.5×10 18 / cm 3 , 2.0×10 18 / cm 3 , 2.5×10 18 / cm 3 , 3.0×10 18 / cm3 etc., not specifically limited here).
[0011] Preferably, the thickness of the doped amorphous silicon layer is 0.5 to 5 nm (for example, 0.5 nm, 1.0 nm, 1.5 nm, 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, 4.5 nm, 5.0 nm, etc., not specifically limited here).
[0012] Preferably, the silicon substrate is N-type, and the thickness of the silicon substrate is 80 to 180 um (for example: 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, etc., not specifically limited here).
[0013] Preferably, the front doped layer and / or the back doped layer also includes a doped microcrystalline silicon layer, the doped microcrystalline silicon layer is deposited on the front passivation layer and / or the back passivation layer, and the doped microcrystalline silicon layer includes at least two sub-doped microcrystalline silicon layers (for example, two layers, three layers, four layers, etc., not specifically limited here).
[0014] Preferably, the thickness of one of the sub-doped microcrystalline silicon layers is 15 to 25 nm (for example, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, etc., not specifically limited herein), and the thickness of the remaining sub-doped layers is 2 to 10 nm (for example, 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, etc., not specifically limited herein).
[0015] The present invention thickens one of the sub-doped layers in the sub-doped microcrystalline silicon layer to a thickness of 15 to 25 nm. The sub-doped layer in this thickness range can better absorb ultraviolet energy, thereby reducing the damage of ultraviolet rays to the battery. If the sub-doped layer is too thick, current will be lost, affecting the conversion efficiency of the battery. If it is too thin, it cannot absorb ultraviolet energy well and cannot achieve the effect of enhancing the resistance to UV radiation.
[0016] Preferably, the doped microcrystalline silicon layer further includes a doped microcrystalline incubation layer, and the doped microcrystalline incubation layer and the sub-doped microcrystalline silicon layer are deposited on the front passivation layer and / or the back passivation layer in a direction away from the silicon substrate.
[0017] Preferably, the thickness of the doped microcrystal incubation layer is 0.5 to 3 nm (eg, 0.5 nm, 1.0 nm, 1.5 nm, 2.0 nm, 2.5 nm, 3.0 nm, etc., not specifically limited herein).
[0018] Preferably, the sub-doped microcrystalline silicon layer includes a first sub-doped microcrystalline silicon layer, and the first sub-doped microcrystalline silicon layer is deposited on the doped microcrystalline incubation layer; the first sub-doped microcrystalline silicon layer is formed in a protective gas atmosphere.
[0019] Preferably, the front passivation layer and / or the back passivation layer further includes at least one intrinsic amorphous silicon layer (eg, one layer, two layers, three layers, etc., not specifically limited here), and the intrinsic amorphous silicon layer is deposited on the oxygen-doped amorphous silicon layer.
[0020] Preferably, the thickness of the oxygen-doped amorphous silicon layer is less than the thickness of the intrinsic amorphous silicon layer, and the thickness of the front passivation layer and / or the back passivation layer is 5 to 15 nm (for example: 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, etc., not specifically limited here).
[0021] In the present invention, the thickness of the first oxygen-doped amorphous silicon layer is smaller than the thickness of the intrinsic amorphous silicon layer in order to enable the intrinsic amorphous silicon layer to play a better passivation role.
[0022] Preferably, the thickness of the front doping layer is 25 to 40 nm (for example, 25 nm, 30 nm, 35 nm, 40 nm, etc., not specifically limited here), and the thickness of the back doping layer is 30 to 45 nm (for example, 30 nm, 35 nm, 40 nm, 45 nm, etc., not specifically limited here); the thickness of the front doping layer is less than the thickness of the back doping layer.
[0023] Since the front side is the sunlight receiving side in the present invention, the thickness of the front doping layer is thinner than that of the back doping layer to facilitate the passage of sunlight, thereby reducing current loss and improving battery conversion efficiency.
[0024] Preferably, the front doped layer is an N-type doped layer, and the back doped layer is a P-type doped layer.
[0025] Preferably, the material of the front transparent conductive layer and / or the back transparent conductive layer is at least one of AZO, ITO, IWO, FTO, and IOH, and the thickness is 80 to 140 nm (for example: 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, etc., not specifically limited here).
[0026] A second aspect of the present invention provides a method for preparing the above-mentioned heterojunction solar cell, comprising the following steps:
[0027] Depositing an oxygen-doped amorphous silicon layer on the front side and / or the back side of the silicon substrate;
[0028] Depositing a doped microcrystalline silicon layer and a doped amorphous silicon layer on the front passivation layer and / or the back passivation layer;
[0029] The steps of depositing doped amorphous silicon are as follows:
[0030] Phosphorus source gas or boron source gas, silicon source gas and H2 are introduced into a very high frequency plasma enhanced chemical vapor deposition (VHF-PECVD) device, wherein the volume ratio of the phosphorus source gas to the silicon source gas is 3.5 to 5.5 times (for example, 3.5 times, 4.0 times, 4.5 times, 5.0 times, 5.5 times, etc., not specifically limited herein), the volume ratio of the boron source gas to the silicon source gas is 1.5 to 3.5 times (for example, 1.5 times, 2.0 times, 2.5 times, 3.0 times, 3.5 times, etc., not specifically limited herein), and the volume ratio of H2 to the silicon source gas is 5 to 35 times (for example, 5 times, 15 times, 25 times, 35 times, etc., not specifically limited herein), the silicon source gas flow rate is 50-500sccm (for example: 50sccm, 100sccm, 150sccm, 200sccm, 250sccm, 300sccm, 350sccm, 400sccm, 450sccm, 500sccm, etc., not specifically limited herein), and the H2 flow rate is 1000-10000sccm (for example: 1000sccm, 2000sccm, 3000sccm, 4000sccm, 5000sccm, 6000sccm, 7000sccm, etc., not specifically limited herein). The flow rate of the phosphorus source gas is 50-200 sccm (for example, 50 sccm, 100 sccm, 150 sccm, 200 sccm, etc., which are not specifically limited here), the flow rate of the boron source gas is 5-100 sccm (for example, 5 sccm, 20 sccm, 40 sccm, 60 sccm, 80 sccm, 100 sccm, etc., which are not specifically limited here), and the temperature is set to 150°C-250°C (for example, 15 The temperature range of the process is 0°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc., not specifically limited herein), the power is 5000-25000W (for example, 5000W, 10000W, 15000W, 20000W, 25000W, etc., not specifically limited herein), and the process pressure is 0.5-3Torr (for example, 0.5Torr, 1.0Torr, 1.5Torr, 2.0Torr, 2.5Torr, 3Torr, etc., not specifically limited herein).
[0031] Preferably, before depositing the oxygen-doped amorphous silicon layer, the method further includes cleaning and texturing the silicon wafer.
[0032] More preferably, the N-type silicon wafer is cleaned with an acid or alkaline compound to remove stains and oxides on the surface.
[0033] More preferably, the pyramid texture is formed on the surface of the silicon wafer by chemical or physical methods.
[0034] Preferably, the step of depositing the oxygen-doped amorphous silicon layer is specifically as follows:
[0035] An oxygen source gas, a silicon source gas and a protective gas are introduced into a very high frequency plasma enhanced chemical vapor deposition (VHF-PECVD) device, wherein the volume ratio of the oxygen source gas to the silicon source gas is 0.01 to 0.5 times (for example, 0.01 times, 0.1 times, 0.2 times, 0.3 times, 0.4 times, 0.5 times, etc., not specifically limited herein), and the volume ratio of the protective gas to the silicon source gas is 0.1 to 1 times (for example, 0.1 times, 0.2 times, 0.3 times, 0.4 times, 0.5 times, 0.6 times, 0.7 times, 0.8 times, 0.9 times, etc., not specifically limited herein). times, 1.0 times, etc., not specifically limited herein), the silicon source gas flow rate is 500-3000sccm (for example: 500sccm, 1000sccm, 1500sccm, 2000sccm, 2500sccm, 3000sccm, etc., not specifically limited herein), and the oxygen source gas flow rate is 10-100sccm (for example: 10sccm, 20sccm, 30sccm, 40sccm, 50sccm, 60sccm, 70sccm, 80sccm, etc. ccm, 90sccm, 100sccm, etc., not specifically limited here), the protective gas flow rate is 500-3000sccm (for example: 500sccm, 1000sccm, 1500sccm, 2000sccm, 2500sccm, 3000sccm, etc., not specifically limited here), and the set temperature is 150℃~250℃ (for example: 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230 ℃, 240℃, 250℃, etc., are not specifically limited here), the power is 500-1500W (for example: 500W, 1000W, 1500W, etc., are not specifically limited here), and the process pressure is 0.1-1.0Torr (for example: 0.1Torr, 0.2Torr, 0.3Torr, 0.4Torr, 0.5Torr, 0.6Torr, 0.7Torr, 0.8Torr, 0.9Torr, 1.0Torr, etc., are not specifically limited here).
[0036] Preferably, after depositing the oxygen-doped amorphous silicon layer, the step of depositing at least one intrinsic amorphous silicon layer thereon (for example, a first intrinsic amorphous silicon layer, a second intrinsic amorphous silicon layer, a third intrinsic amorphous silicon layer, etc., which are not specifically limited herein) is further included, specifically:
[0037] In a Very High Frequency Plasma Enhanced Chemical Vapor Deposition (VHF-PECVD) device, silicon source gas and H2 are introduced, the volume ratio of H2 to silicon source gas is 0.5 to 2 times (for example, 0.5 times, 1.0 times, 1.5 times, 2.0 times, etc., not specifically limited herein), the flow rate of silicon source gas is 1000 to 3000 sccm (for example, 1000 sccm, 1500 sccm, 2000 sccm, 2500 sccm, 3000 sccm, etc., not specifically limited herein), and the flow rate of H2 is 1000 to 3000 sccm (for example, 1000 sccm, 1500 sccm, 2000 sccm, 2500 sccm, 3000 sccm, etc., not specifically limited herein), and the The setting temperature is 150-250°C (for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc., not limited to the specific examples), the process pressure is 0.5-1.5 Torr (for example, 0.5 Torr, 0.6 Torr, 0.7 Torr, 0.8 Torr, 0.9 Torr, 1.0 Torr, 1.1 Torr, 1.2 Torr, 1.3 Torr, 1.4 Torr, 1.5 Torr, etc., not limited to the specific examples), and the power is 500-1500 W (for example, 500 W, 1000 W, 1500 W, etc., not limited to the specific examples).
[0038] After the deposition of the oxygen-doped amorphous silicon layer and the intrinsic amorphous silicon layer is completed, the deposition of the front passivation layer and the back passivation layer is completed.
[0039] Preferably, depositing the doped microcrystalline silicon layer includes depositing at least two sub-doped microcrystalline silicon layers (for example: a first sub-doped microcrystalline silicon layer, a second sub-doped microcrystalline silicon layer, a third sub-doped microcrystalline silicon layer, etc., not specifically limited herein), wherein the thickness of one sub-doped microcrystalline silicon layer is 15 to 25 nm (for example: 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 25 nm, etc., not specifically limited herein).
[0040] Preferably, before depositing the sub-doped microcrystalline silicon layer, a step of depositing a doped microcrystalline silicon incubation layer is also included, specifically:
[0041] Phosphorus source gas or boron source gas, oxygen source gas, silicon source gas and H2 are introduced into a very high frequency plasma enhanced chemical vapor deposition (VHF-PECVD) device, wherein the volume ratio of the phosphorus source gas to the silicon source gas is 0.5 to 3.5 times (for example, 0.5 times, 1.0 times, 1.5 times, 2.0 times, 2.5 times, 3.0 times, 3.5 times, etc., not specifically limited herein), and the volume ratio of the boron source gas to the silicon source gas is 0.05 to 1.0 times (for example, 0.05 times, 0.1 times, 0.2 times, 0.3 times, 0.5 times, etc., not specifically limited herein). 4 times, 0.5 times, 0.6 times, 0.7 times, 0.8 times, 0.9 times, 1.0 times, etc., not specifically limited here), the silicon source gas flow rate is 50-500sccm (for example: 50sccm, 100sccm, 150sccm, 200sccm, 250sccm, 300sccm, 350sccm, 400sccm, 450sccm, 500sccm, etc., not specifically limited here), and the H2 flow rate is 20000-50000scc m (for example: 20000sccm, 25000sccm, 30000sccm, 35000sccm, 40000sccm, 45000sccm, 50000sccm, etc., not specifically limited here), the phosphorus source gas flow rate is 100-500sccm (for example: 100sccm, 200sccm, 300sccm, 400sccm, 500sccm, etc., not specifically limited here), and the temperature is set to 150-250°C (for example Such as: 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, etc., not specifically limited here), the process pressure is 2~6Torr (for example: 2Torr, 3Torr, 4Torr, 5Torr, 6Torr, etc., not specifically limited here), the power is 5000~15000W (for example: 5000W, 10000W, 15000W, etc., not specifically limited here).
[0042] Preferably, depositing the sub-doped microcrystalline silicon layer includes the step of first depositing a first sub-doped microcrystalline silicon layer, and the first sub-doped microcrystalline silicon layer is deposited in a protective gas atmosphere. The types, flow rates, volume ratios with silicon source gases, set temperatures, process pressures, and powers of other process gases are the same as those of depositing the doped microcrystalline silicon incubation layer. The volume ratio of the protective gas to the silicon source gas is 0.5 to 25 times (for example, 0.5, 5.5, 10.5, 15.5, 20.5, 25, etc., not specifically limited herein), and the protective gas flow rate is 50 to 500 sccm (for example: 50 sccm, 100 sccm, 150 sccm, 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, 500 sccm, etc., not specifically limited herein).
[0043] Preferably, when depositing the remaining sub-doped microcrystalline silicon layers (for example, the second sub-doped microcrystalline silicon layer, the third sub-doped microcrystalline silicon layer, etc., which are not specifically limited here) on the first sub-doped microcrystalline silicon layer, the deposition is not carried out under a protective gas atmosphere, and the types, flow rates, volume ratios with the silicon source gas, set temperatures, process pressures, and powers of the remaining process gases are the same as those for depositing the doped microcrystalline silicon incubation layer.
[0044] Preferably, when depositing the doped microcrystalline silicon layer, when the phosphorus source gas is introduced, the volume ratio of the oxygen source gas to the silicon source gas is 0.5 to 3.5 times (for example, 0.5 times, 1.0 times, 1.5 times, 2.0 times, 2.5 times, 3.0 times, 3.5 times, etc., not specifically limited herein), and the flow rate of the oxygen source gas is 50 to 500 sccm (for example, 50 sccm, 100 sccm, 150 sccm, 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, 500 sccm, etc., not specifically limited herein);
[0045] When the boron source gas is introduced, the volume ratio of the oxygen source gas to the silicon source gas is 0.05 to 1.0 times (for example, 0.05 times, 0.1 times, 0.2 times, 0.3 times, 0.4 times, 0.5 times, 0.6 times, 0.7 times, 0.8 times, 0.9 times, 1.0 times, etc., not specifically limited here), and the oxygen source gas flow rate is 5 to 50 sccm (for example: 5 sccm, 15 sccm, 25 sccm, 35 sccm, 45 sccm, 50 sccm, etc., not specifically limited here).
[0046] After the deposition of the doped microcrystalline silicon layer and the doped amorphous silicon layer is completed, the deposition of the front doped layer and the back doped layer is completed.
[0047] The process gas in the present invention is a gas that directly or indirectly participates in the production process in industrial production and is used to control and improve the production process, specifically a boron source gas, a phosphorus source gas, a silicon source gas, an oxygen source gas, a protective gas, and H2. The boron source gas is a gas that provides boron atoms, the phosphorus source gas is a gas that provides phosphorus atoms, the silicon source gas is a gas that provides silicon atoms, the oxygen source gas is a gas that provides oxygen atoms, and the protective gas is an inert gas.
[0048] Preferably, the boron source gas is one of BH3 and TMB, the phosphorus source gas is one of PH3 and POCl3, the oxygen source gas is one of CO2 and N2O, and the silicon source gas is SiH4.
[0049] Preferably, the protective gas is nitrogen, argon, helium, neon, krypton, xenon or a mixture thereof.
[0050] Preferably, a PVD automated device is used to deposit the front doped layer to form a front transparent conductive layer, and to deposit the back doped layer to form a back transparent conductive layer.
[0051] Preferably, a front metal electrode is provided on the front transparent conductive layer, and a back metal electrode is provided on the back transparent conductive layer by using a silk screen automated equipment.
[0052] The third aspect of the present invention provides a photovoltaic module composed of the above-mentioned heterojunction solar cell.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] The present invention deposits an oxygen-doped amorphous silicon layer and a doped amorphous silicon layer on the front and / or back of the battery, and the hydrogen atom concentration of the doped amorphous silicon layer is 4.5×10 19 / cm 3 ~5.5×10 19 / cm 3 , the doping concentration of phosphorus or boron is 5.0×10 17 / cm 3 ~5.0×10 19 / cm 3 , enhancing its resistance to UV radiation, specifically: depositing an oxygen-doped amorphous silicon layer, which helps to optimize the deposition environment, reduce the formation of impurities and defects, thereby improving the quality and uniformity of amorphous silicon films and enhancing the passivation effect; depositing a doped amorphous silicon layer, the hydrogen atom concentration of the doped amorphous silicon layer is 4.5×10 19 / cm 3 ~5.5×10 19 / cm 3The silicon-hydrogen bond is relatively stable within the range and is not easy to break, thus reducing the damage of ultraviolet rays to the internal structure of the battery; the light absorption characteristics of the doped amorphous silicon layer are different from those of microcrystalline silicon. By adjusting the doping concentration of the doped amorphous silicon layer, the doping concentration of phosphorus or boron in the doped amorphous silicon layer is within 5.0×10 17 / cm 3 ~5.0×10 19 / cm 3 The spectral response characteristics of the battery can be optimized to better match the ultraviolet band in the solar spectrum, which helps to improve the battery's absorption and utilization efficiency of ultraviolet rays. The interface between the doped amorphous silicon layer and the transparent conductive layer is smoother, reducing the reflection and transmission losses of light at the interface, which allows more ultraviolet rays to enter the battery and be effectively absorbed and converted. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 Schematic diagram of the structure of the heterojunction solar cell in Example 1-3, the arrow points to the sunlight receiving surface of the heterojunction cell, i.e., the front side, in the figure: 0-N-type silicon substrate, 111-front oxygen-doped amorphous silicon layer, 112-front first intrinsic amorphous silicon layer, 113-front second intrinsic amorphous silicon layer, 114-front N-type doped microcrystalline silicon incubation layer, 115-front first N-type sub-doped microcrystalline silicon layer, 116-front second N-type sub-doped microcrystalline silicon layer, 117-front third N-type sub-doped microcrystalline silicon layer, 118-front doped amorphous silicon layer, 119-front ITO transparent conductive layer, 120-front metal electrode, 221-back oxygen-doped amorphous silicon layer, 222-back first intrinsic amorphous silicon layer, 223-back second intrinsic amorphous silicon layer, 224-back P-type doped microcrystalline silicon incubation layer, 225-back first P-type sub-doped microcrystalline silicon layer, 226-back second P-type sub-doped microcrystalline silicon layer, 227-back third P-type sub-doped microcrystalline silicon layer, 228-back P-type doped amorphous silicon layer, 229-back ITO transparent conductive layer, 230-back metal electrode. DETAILED DESCRIPTION
[0056] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0057] The heterojunction solar cell and the preparation method thereof of the present invention are further described below through specific examples and comparative examples.
[0058] Example 1
[0059] like Figure 1 As shown, an N-type heterojunction solar cell comprises an N-type silicon substrate 0, and the front side of the silicon substrate is provided with a front oxygen-doped amorphous silicon layer 111, a front first intrinsic amorphous silicon layer 112, a front second intrinsic amorphous silicon layer 113, a front N-type doped microcrystalline silicon incubation layer 114, a front first N-type sub-doped microcrystalline silicon layer 115, a front second N-type sub-doped microcrystalline silicon layer 116, a front third N-type sub-doped microcrystalline silicon layer 117, a front N-type doped amorphous silicon layer 118, and a front ITO transparent conductive layer 119 in sequence from the inside to the outside. 119, front metal electrode 120; the front side of the silicon substrate is provided with a back oxygen-doped amorphous silicon layer 221, a back first intrinsic amorphous silicon layer 222, a back second intrinsic amorphous silicon layer 223, a back P-type doped microcrystalline silicon incubation layer 224, a back first P-type sub-doped microcrystalline silicon layer 225, a back second P-type sub-doped microcrystalline silicon layer 226, a back third P-type sub-doped microcrystalline silicon layer 227, a back P-type doped amorphous silicon layer 228, a back ITO transparent conductive layer 229, and a back metal electrode 230 in sequence from the inside to the outside;
[0060] The hydrogen atomic concentration of the front N-type doped amorphous silicon layer 118 and the back P-type doped amorphous silicon layer 228 is 5.0×10 19 / cm 3 , the doping concentration of phosphorus or boron is 7.5×10 18 / cm 3 .
[0061] The method for preparing an N-type solar cell in this embodiment includes the following steps:
[0062] 1. Select N-type silicon substrate with a thickness of 130μm for bottom cleaning to remove organic dirt, metal impurities and surface damage layer on the surface.
[0063] 2. After cleaning, texturing is performed to form a suede layer on the front and back sides of the N-type silicon substrate 0.
[0064] 3. Place the N-type silicon substrate 0 after texturing in a VHF-PECVD chamber, introduce SiH4, CO2, and Ar, the SiH4 flow rate is 2000sccm, the CO2 flow rate is 50sccm, the volume ratio of CO2 to SiH4 is 0.3 times, the Ar flow rate is 2000sccm, the volume ratio of Ar to SiH4 is 0.6 times, the chamber temperature is 200℃, the process pressure is 0.6Torr, the power is 1000W, and a back oxygen-doped amorphous silicon layer 221 is prepared on the back of the N-type silicon substrate 0 , with a thickness of 1.5nm; SiH4 and H2 process gases are introduced, with a SiH4 flow rate of 2000sccm, a H2 flow rate of 2000sccm, a volume ratio of H2 to SiH4 of 1.5 times, a chamber temperature of 200°C, a process pressure of 1.0Torr, and a power of 1000W, and a first back intrinsic amorphous silicon layer 222 and a second back intrinsic amorphous silicon layer 223 are sequentially deposited on the back oxygen-doped amorphous silicon layer 221, with a thickness of 3.5nm, that is, the back passivation layer of the silicon wafer has been deposited;
[0065] The silicon wafer is then turned over by an automated flipping device, and the same process steps are followed on the front side of the silicon wafer to complete the deposition of the front oxygen-doped amorphous silicon layer 111, the front first intrinsic amorphous silicon layer 112, and the front second intrinsic amorphous silicon layer 113, that is, the deposition of the front passivation layer is completed.
[0066] 4. After completing step 3 above, SiH4, H2, PH3, and CO2 are introduced. The SiH4 flow rate is 250sccm, the H2 flow rate is 35000sccm, the PH3 flow rate is 300sccm, the CO2 flow rate is 300sccm, the volume ratio of PH3 to SiH4 is 2.0 times, the volume ratio of CO2 to SiH4 is 2.0 times, and the volume ratio of H2 to SiH4 is 150 times. The chamber temperature is 200°C, the process pressure is 4Torr, the power is 10000W, and a positive passivation layer is deposited on the front side to form a positive passivation layer. The surface N-type doped microcrystalline silicon incubation layer 114 has a thickness of 2nm; SiH4, H2, PH3, CO2, and Ar are introduced, the SiH4 flow rate is 250sccm, the H2 flow rate is 35000sccm, the PH3 flow rate is 300sccm, the CO2 flow rate is 300sccm, the volume ratio of PH3 to SiH4 is 2.0 times, the volume ratio of CO2 to SiH4 is 2.0 times, the volume ratio of H2 to SiH4 is 150, the Ar flow rate is 300sccm, and the volume ratio of Ar to SiH4 is 15.5 times , the chamber temperature is 200°C, the process pressure is 4Torr, the power is 10000W, a front first N-type sub-doped microcrystalline silicon layer 115 is deposited on the front N-type doped microcrystalline silicon incubation layer 114, the thickness of which is 20nm, and the steps of depositing the front N-type doped microcrystalline silicon incubation layer 114 are repeated to sequentially deposit a front second N-type sub-doped microcrystalline silicon layer 116 and a front third N-type sub-doped microcrystalline silicon layer 117 on the front first N-type sub-doped microcrystalline silicon layer 115, the thickness of which are both 5nm; SiH4, H2, and PH3 are introduced, wherein SiH 4 flow rate is 275sccm, H2 flow rate is 5500sccm, PH3 flow rate is 125sccm, wherein the volume ratio of PH3 to SiH4 is 4.5 times, the volume ratio of H2 to SiH4 is 20 times, the chamber temperature is 200°C, the process pressure is 2.0Torr, the power is 15000W, and a front N-type doped amorphous silicon layer 118 is deposited on the front third N-type sub-doped microcrystalline silicon layer 117, with a thickness of 2.5nm, that is, the front N-type doped layer is deposited, and the thickness of the front N-type doped layer is 34.5nm;
[0067] Subsequently, the silicon wafer is turned over by an automated flipping device, and the deposition of a back P-type doped microcrystalline silicon incubation layer 224, a back first P-type sub-doped microcrystalline silicon layer 225, a back second P-type sub-doped microcrystalline silicon layer 226, a back third P-type sub-doped microcrystalline silicon layer 227 is different from the deposition of a front N-type doped microcrystalline silicon incubation layer 114, a front first N-type sub-doped microcrystalline silicon layer 115, a front second N-type sub-doped microcrystalline silicon layer 116, and a front third N-type sub-doped microcrystalline silicon layer 117 in that: PH3 is replaced by B2H6, the flow rate of B2H6 is 100 sccm, the flow rate of CO2 is 25 sccm, the volume ratio of B2H6 to SiH4 is 0.5 times, the volume ratio of CO2 to SiH4 is 0.5 times, the thicknesses are 2 nm, 25 nm, 6 nm, and 6 nm respectively, and the rest are the same;
[0068] The difference between depositing the back P-type doped amorphous silicon layer 228 and depositing the front N-type doped amorphous silicon layer 118 is that PH3 is replaced by B2H6, the flow rate of B2H6 is 52 sccm, the volume ratio of B2H6 to SiH4 is 2.5 times, the thickness is 3 nm, and the rest are the same;
[0069] The deposition of the above-mentioned back P-type doped microcrystalline silicon incubation layer 224, the back first P-type sub-doped microcrystalline silicon layer 225, the back second P-type sub-doped microcrystalline silicon layer 226, the back third P-type sub-doped microcrystalline silicon layer 227, and the back P-type doped amorphous silicon layer 228 is completed, that is, the back P-type doped layer deposition is completed.
[0070] 5. The PVD technology is used for film formation. The target material is In2O3 / SnO2 with a mass ratio of 97:3. The film forming temperature is 200°C. The front ITO transparent conductive layer 119 and the back ITO transparent conductive layer 229 are deposited, and the thickness is 120nm.
[0071] 6. Use a screen printing automation device to set a front metal electrode 120 on the front ITO transparent conductive layer 119 , and set a back metal electrode 230 on the back ITO transparent conductive layer 229 .
[0072] Example 2
[0073] like Figure 1As shown, an N-type heterojunction solar cell comprises an N-type silicon substrate 0, and the front side of the silicon substrate is provided with a front oxygen-doped amorphous silicon layer 111, a front first intrinsic amorphous silicon layer 112, a front second intrinsic amorphous silicon layer 113, a front N-type doped microcrystalline silicon incubation layer 114, a front first N-type sub-doped microcrystalline silicon layer 115, a front second N-type sub-doped microcrystalline silicon layer 116, a front third N-type sub-doped microcrystalline silicon layer 117, a front N-type doped amorphous silicon layer 118, and a front ITO transparent conductive layer 119 in sequence from the inside to the outside. 19. Front metal electrode 120; the front side of the silicon substrate is provided with a back oxygen-doped amorphous silicon layer 221, a back first intrinsic amorphous silicon layer 222, a back second intrinsic amorphous silicon layer 223, a back P-type doped microcrystalline silicon incubation layer 224, a back first P-type sub-doped microcrystalline silicon layer 225, a back second P-type sub-doped microcrystalline silicon layer 226, a back third P-type sub-doped microcrystalline silicon layer 227, a back P-type doped amorphous silicon layer 228, a back ITO transparent conductive layer 229, and a back metal electrode 230 in sequence from the inside to the outside;
[0074] The hydrogen atomic concentration of the front N-type doped amorphous silicon layer 118 and the back P-type doped amorphous silicon layer 228 is 4.5×10 19 / cm 3 , the doping concentration of phosphorus or boron is 5.0×10 17 / cm 3 .
[0075] The method for preparing an N-type heterojunction solar cell in this embodiment includes the following steps:
[0076] 1. Select N-type silicon substrate with a thickness of 80μm for bottom cleaning to remove organic dirt, metal impurities and surface damage layer on the surface.
[0077] 2. After cleaning, texturing is performed to form a suede layer on the front and back sides of the N-type silicon substrate 0.
[0078] 3. Place the N-type silicon wafer 0 after texturing in a VHF-PECVD chamber, introduce SiH4, CO2, and Ar, the SiH4 flow rate is 500sccm, the CO2 flow rate is 10sccm, the volume ratio of CO2 to SiH4 is 0.01 times, the Ar flow rate is 500sccm, the volume ratio of Ar to SiH4 is 1.0 times, the chamber temperature is 150℃, the process pressure is 0.1Torr, the power is 500W, and a back oxygen-doped amorphous silicon layer 221 is prepared on the back of the silicon wafer , with a thickness of 0.5nm; SiH4 and H2 are introduced, the SiH4 flow rate is 1000sccm, the H2 flow rate is 1000sccm, the volume ratio of H2 to SiH4 is 0.5 times, the chamber temperature is 150°C, the process pressure is 0.5Torr, the power is 500W, and a first back intrinsic amorphous silicon layer 222 and a second back intrinsic amorphous silicon layer 223 are sequentially deposited on the back oxygen-doped amorphous silicon layer 221, and the thickness is 0.5nm, that is, the back passivation layer of the silicon wafer has been deposited;
[0079] The silicon wafer is then turned over by an automated flipping device, and the same process steps are followed on the front side of the silicon wafer to complete the deposition of the front oxygen-doped amorphous silicon layer 111, the front first intrinsic amorphous silicon layer 112, and the front second intrinsic amorphous silicon layer 113, that is, the deposition of the front passivation layer is completed.
[0080] 4. After completing step 3 above, SiH4, H2, PH3, and CO2 are introduced. The SiH4 flow rate is 50sccm, the H2 flow rate is 20000sccm, the PH3 flow rate is 100sccm, the CO2 flow rate is 50sccm, the volume ratio of PH3 to SiH4 is 0.5 times, the volume ratio of CO2 to SiH4 is 0.5 times, and the volume ratio of H2 to SiH4 is 50 times. The chamber temperature is 150°C, the process pressure is 2Torr, the power is 5000W, and a positive passivation layer is deposited on the front side to form a positive passivation layer. The surface N-type doped microcrystalline silicon incubation layer 114 has a thickness of 0.5nm; SiH4, H2, PH3, CO2, and Ar are introduced, the SiH4 flow rate is 50sccm, the H2 flow rate is 20000sccm, the PH3 flow rate is 100sccm, the CO2 flow rate is 50sccm, the volume ratio of PH3 to SiH4 is 0.5 times, the volume ratio of CO2 to SiH4 is 0.5 times, the volume ratio of H2 to SiH4 is 50 times, the Ar flow rate is 50sccm, and the volume ratio of Ar to SiH4 is 0.5 times, the chamber temperature is 150°C, the process pressure is 2Torr, the power is 5000W, a front first N-type sub-doped microcrystalline silicon layer 115 is deposited on the front N-type doped microcrystalline silicon incubation layer 114, and the thickness is 15nm. The steps of depositing the front N-type microcrystalline silicon incubation layer 114 are repeated to sequentially deposit a front second N-type sub-doped microcrystalline silicon layer 116 and a front third N-type sub-doped microcrystalline silicon layer 117 on the front first N-type sub-doped microcrystalline silicon layer 115, and the thicknesses are both 10nm; SiH4, H2, and PH3 are introduced, and the thickness of the first N-type sub-doped microcrystalline silicon layer 116 is formed. The SiH4 flow rate is 50sccm, the H2 flow rate is 1000sccm, and the PH3 flow rate is 50sccm, wherein the volume ratio of PH3 to SiH4 is 3.5 times, the volume ratio of H2 to SiH4 is 5 times, the chamber temperature is 150°C, the process pressure is 0.5Torr, the power is 5000W, and a front N-type doped amorphous silicon layer 118 is deposited on the front third N-type sub-doped microcrystalline silicon layer 117, with a thickness of 0.5nm, that is, the front doped layer is deposited, and the thickness of the front doped layer is 26nm;
[0081] Subsequently, the silicon wafer is turned over by an automated flipping device, and the deposition of a back P-type doped microcrystalline silicon incubation layer 224, a back first P-type sub-doped microcrystalline silicon layer 225, a back second P-type sub-doped microcrystalline silicon layer 226, a back third P-type sub-doped microcrystalline silicon layer 227 is different from the deposition of a front N-type doped microcrystalline silicon incubation layer 114, a front first N-type sub-doped microcrystalline silicon layer 115, a front second N-type sub-doped microcrystalline silicon layer 116, and a front third N-type sub-doped microcrystalline silicon layer 117 in that: PH3 is replaced by B2H6, the flow rate of B2H6 is 10sccm, the flow rate of CO2 is 5sccm, the volume ratio of B2H6 to SiH4 is 0.05 times, the volume ratio of CO2 to SiH4 is 0.05 times, the thicknesses are 0.5nm, 15nm, 10nm, 10nm respectively, and the rest are the same;
[0082] The difference between depositing the back P-type doped amorphous silicon layer 228 and depositing the front N-type doped amorphous silicon layer 118 is that PH3 is replaced by B2H6, the flow rate of B2H6 is 5 sccm, the volume ratio of B2H6 to SiH4 is 1.5 times, the thickness is 0.5 nm, and the rest are the same;
[0083] The deposition of the above-mentioned back P-type doped microcrystalline silicon incubation layer 224, the back first P-type sub-doped microcrystalline silicon layer 225, the back second P-type sub-doped microcrystalline silicon layer 226, the back third P-type sub-doped microcrystalline silicon layer 227, and the back P-type doped amorphous silicon layer 228 is completed, that is, the back P-type doped layer deposition is completed.
[0084] 5. The PVD technology is used for film formation. The target material is In2O3 / SnO2 with a mass ratio of 97:3. The film forming temperature is 200°C. The front ITO transparent conductive layer 119 and the back ITO transparent conductive layer 229 are deposited with a thickness of 80nm.
[0085] 6. Use a screen printing automation device to set a front metal electrode 120 on the front ITO transparent conductive layer 119 , and set a back metal electrode 230 on the back ITO transparent conductive layer 229 .
[0086] Example 3
[0087] like Figure 1As shown, an N-type heterojunction solar cell comprises an N-type silicon substrate 0, and the front side of the silicon substrate is provided with a front oxygen-doped amorphous silicon layer 111, a front first intrinsic amorphous silicon layer 112, a front second intrinsic amorphous silicon layer 113, a front N-type doped microcrystalline silicon incubation layer 114, a front first N-type sub-doped microcrystalline silicon layer 115, a front second N-type sub-doped microcrystalline silicon layer 116, a front third N-type sub-doped microcrystalline silicon layer 117, a front N-type doped amorphous silicon layer 118, and a front ITO transparent conductive layer 119 in sequence from the inside to the outside. 9. The front metal electrode 120; the front side of the silicon substrate is provided with a back oxygen-doped amorphous silicon layer 221, a back first intrinsic amorphous silicon layer 222, a back second intrinsic amorphous silicon layer 223, a back P-type doped microcrystalline silicon incubation layer 224, a back first P-type sub-doped microcrystalline silicon layer 225, a back second P-type sub-doped microcrystalline silicon layer 226, a back third P-type sub-doped microcrystalline silicon layer 227, a back P-type doped amorphous silicon layer 228, a back ITO transparent conductive layer 229, and a back metal electrode 230 in sequence from the inside to the outside;
[0088] The hydrogen atomic concentration of the front N-type doped amorphous silicon layer 118 and the back P-type doped amorphous silicon layer 228 is 5.5×10 19 / cm 3 , the doping concentration of phosphorus or boron is 5.0×10 19 / cm 3 .
[0089] The method for preparing an N-type heterojunction solar cell in this embodiment includes the following steps:
[0090] 1. Select N-type silicon substrate with a thickness of 180μm for bottom cleaning to remove organic dirt, metal impurities and surface damage layer on the surface.
[0091] 2. After cleaning, texturing is performed to form a suede layer on the front and back sides of the N-type silicon substrate 0.
[0092] 3. Place the N-type silicon wafer 0 after texturing in a VHF-PECVD chamber, introduce SiH4, CO2, and Ar, the SiH4 flow rate is 3000sccm, the CO2 flow rate is 100sccm, the volume ratio of CO2 to SiH4 is 0.5 times, the Ar flow rate is 3000sccm, the volume ratio of Ar to SiH4 is 0.1 times, the chamber temperature is 250°C, the process pressure is 1.0Torr, the power is 1500W, and a back oxygen-doped amorphous silicon layer 221 with a thickness of 2.5nm is prepared on the back of the silicon wafer; introduce SiH4 and H2, the SiH4 flow rate is 3000sccm, the H2 flow rate is 300 0sccm, the volume ratio of H2 to SiH4 is 2.0 times, the chamber temperature is 250℃, the process pressure is 1.5Torr, the power is 1500W, and a first intrinsic amorphous silicon layer 222 and a second intrinsic amorphous silicon layer 223 are sequentially deposited on the back oxygen-doped amorphous silicon layer 221, and the thickness of each layer is 5nm, that is, the back passivation layer of the silicon wafer has been deposited; then, the silicon wafer is turned over by an automated flipping equipment, and the front side of the silicon wafer is deposited according to the same process steps, and the front oxygen-doped amorphous silicon layer 111, the first intrinsic amorphous silicon layer 112, and the second intrinsic amorphous silicon layer 113 are deposited respectively, that is, the front passivation layer deposition is completed.
[0093] 4. After completing step 3, SiH4, H2, PH3, and CO2 are introduced, the SiH4 flow rate is 500sccm, the H2 flow rate is 50000sccm, the PH3 flow rate is 500sccm, the CO2 flow rate is 500sccm, the volume ratio of PH3 to SiH4 is 3.5 times, the volume ratio of CO2 to SiH4 is 3.5 times, the volume ratio of H2 to SiH4 is 200 times, the chamber temperature is 250°C, the process pressure is 6Torr, the power is 15000W, and the front passivation layer is Deposition forms a front N-type doped microcrystalline silicon incubation layer 114 with a thickness of 3nm; SiH4, H2, PH3, CO2, and Ar are introduced, the SiH4 flow rate is 500sccm, the H2 flow rate is 50000sccm, the PH3 flow rate is 500sccm, the CO2 flow rate is 500sccm, the volume ratio of PH3 to SiH4 is 3.5 times, the volume ratio of CO2 to SiH4 is 3.5 times, the volume ratio of H2 to SiH4 is 200 times, the Ar flow rate is 500sccm, and the Ar and SiH4 ratio is 200 times. The volume ratio is 25 times, the chamber temperature is 250°C, the process pressure is 6Torr, the power is 15000W, and a front first N-type sub-doped microcrystalline silicon layer 115 is deposited on the front microcrystalline silicon incubation layer 114, with a thickness of 25nm. The steps of depositing the front N-type doped microcrystalline silicon incubation layer 114 are repeated to sequentially deposit a front second N-type sub-doped microcrystalline silicon layer 116 and a front third N-type sub-doped microcrystalline silicon layer 117 on the front first N-type sub-doped microcrystalline silicon layer 115, with a thickness of 2nm. SiH4, H2, and PH3 are introduced. The SiH4 flow rate is 500sccm, the H2 flow rate is 10000sccm, and the PH3 flow rate is 200sccm, wherein the volume ratio of PH3 to SiH4 is 5.5 times, the volume ratio of H2 to SiH4 is 35 times, the chamber temperature is 250°C, the process pressure is 3.0Torr, the power is 20000W, and a front N-type doped amorphous silicon layer 118 is deposited on the front third N-type sub-doped microcrystalline silicon layer 117, with a thickness of 5nm, that is, the front doped layer is deposited, and the thickness of the front doped layer is 37nm;
[0094] Subsequently, the silicon wafer is turned over by an automated flipping device, and the deposition of a back P-type doped microcrystalline silicon incubation layer 224, a back first P-type sub-doped microcrystalline silicon layer 225, a back second P-type sub-doped microcrystalline silicon layer 226, a back third P-type sub-doped microcrystalline silicon layer 227 is different from the deposition of a front N-type doped microcrystalline silicon incubation layer 114, a front first N-type sub-doped microcrystalline silicon layer 115, a front second N-type sub-doped microcrystalline silicon layer 116, and a front third N-type sub-doped microcrystalline silicon layer 117 in that: PH3 is replaced by B2H6, the flow rate of B2H6 is 200 sccm, the flow rate of CO2 is 50 sccm, the volume ratio of B2H6 to SiH4 is 1.0 times, the volume ratio of CO2 to SiH4 is 1.0 times, the thicknesses are 3 nm, 25 nm, 5 nm, and 5 nm respectively, and the rest are the same;
[0095] The difference between depositing the back P-type doped amorphous silicon layer 228 and depositing the front N-type doped amorphous silicon layer 118 is that PH3 is replaced by B2H6, the flow rate of B2H6 is 100 sccm, the volume ratio of B2H6 to SiH4 is 3.5 times, the thickness is 5 nm, and the rest are the same;
[0096] The deposition of the above-mentioned back P-type microcrystalline silicon incubation layer 224, the back first P-type sub-doped microcrystalline silicon layer 225, the back second P-type sub-doped microcrystalline silicon layer 226, the back third P-type sub-doped microcrystalline silicon layer 227, and the back P-type doped amorphous silicon layer 228 is completed, that is, the back P-type doped layer deposition is completed.
[0097] 5. The PVD technology is used for film formation. The target material is In2O3 / SnO2 with a mass ratio of 97:3. The film forming temperature is 200°C. The front ITO transparent conductive layer 119 and the back ITO transparent conductive layer 229 are deposited, and the thickness is 140nm.
[0098] 6. Use a screen printing automation device to set a front metal electrode 120 on the front ITO transparent conductive layer 119 , and set a back metal electrode 230 on the back ITO transparent conductive layer 229 .
[0099] Example 4
[0100] The preparation method of this embodiment is different from that of Embodiment 1 in that: the thickness of the first N-type sub-doped microcrystalline silicon layer and the third N-type sub-doped microcrystalline silicon layer deposited on the front side in step 4 are both 5 nm, and the thickness of the second N-type doped microcrystalline silicon layer on the front side is 20 nm; the remaining steps are the same.
[0101] Example 5
[0102] The preparation method of this embodiment is different from that of Embodiment 1 in that: the thickness of the first N-type sub-doped microcrystalline silicon layer and the second N-type sub-doped microcrystalline silicon layer deposited on the front side in step 4 are both 5 nm, and the thickness of the third N-type doped microcrystalline silicon layer on the front side is 20 nm; the remaining steps are the same.
[0103] Example 6
[0104] The preparation method of this embodiment is different from that of Embodiment 1 in that: the Ar used in depositing the front oxygen-doped amorphous silicon layer and the back oxygen-doped amorphous silicon layer in step 3, and the Ar used in depositing the front first N-type sub-doped microcrystalline silicon layer and the back first P-type sub-doped microcrystalline silicon layer in step 4 are replaced by N2, and the remaining steps are the same.
[0105] Example 7
[0106] The preparation method of this embodiment is different from that of Embodiment 1 in that the PH3 for depositing the front doping layer in step 4 is replaced by POCl3, and the remaining steps are the same.
[0107] Example 8
[0108] The preparation method of this embodiment is different from that of Embodiment 1 in that the B2H6 used to deposit the back doping layer in step 4 is replaced by TMB, and the other steps are the same.
[0109] Example 9
[0110] The preparation method of this embodiment is different from that of Embodiment 1 in that: the CO2 used in depositing the back oxygen-doped amorphous silicon layer and the front oxygen-doped amorphous silicon layer in step 3 and the CO2 used in depositing the back doped microcrystalline silicon layer and the front doped microcrystalline silicon layer in step 4 are replaced by N2O, and the remaining steps are the same.
[0111] Example 10
[0112] The preparation method of this embodiment is different from that of Embodiment 1 in that: in step 3, no back oxygen-doped amorphous silicon layer is deposited on the back side, and the remaining steps are the same.
[0113] Embodiment 11
[0114] The preparation method of this embodiment is different from that of Embodiment 1 in that: in step 4, no back P-type doped amorphous silicon layer is deposited on the back side, and the remaining steps are the same.
[0115] Example 12
[0116] The preparation method of this embodiment is different from that of Embodiment 1 in that: in step 4, the back side first P-type doped microcrystalline silicon layer is not deposited in argon gas, and the other steps are the same.
[0117] Comparative Example 1
[0118] The battery structure of this comparative example is different from that of Example 2 in that the hydrogen atom concentrations of the front N-type doped amorphous silicon layer 118 and the back P-type doped amorphous silicon layer 228 are both 4.4×10 19 / cm 3 , the doping concentration of phosphorus or boron is 0.4×10 18 / cm 3 , and the rest are the same.
[0119] The preparation method of this comparative example is different from that of Example 2 in that: when depositing the front N-type doped amorphous silicon layer in step 4, the SiH4 flow rate is 45sccm, the H2 flow rate is 950sccm, the PH3 flow rate is 45sccm, the volume ratio of PH3 to SiH4 is 3.2 times, the volume ratio of H2 to SiH4 is 4.8 times, the chamber temperature is 150°C, the process pressure is 0.5Torr, and the power is 5000W; when depositing the back P-type doped amorphous silicon layer, PH3 is replaced by B2H6 gas, the B2H6 flow rate is 4sccm, and the volume ratio of B2H6 to SiH4 is 1.4 times; the remaining steps are the same.
[0120] Comparative Example 2
[0121] The battery structure of this comparative example is different from that of Example 1 in that the front N-type doped amorphous silicon layer and the back P-type doped amorphous silicon layer are replaced by the front N-type doped microcrystalline silicon layer and the back P-type doped microcrystalline silicon layer, and the doping concentration of phosphorus or boron is 7.5×10 18 / cm 3 , and the rest are the same.
[0122] The preparation method of this comparative example is different from that of Example 1, except that: in step 4, a front N-type doped microcrystalline silicon layer is deposited, wherein the SiH4 flow rate is 250sccm, the H2 flow rate is 35000sccm, the PH3 flow rate is 300sccm, the CO2 flow rate is 300sccm, the volume ratio of PH3 to SiH4 is 2.0 times, the volume ratio of CO2 to SiH4 is 2.0 times, the volume ratio of H2 to SiH4 is 150 times, the chamber temperature is 200°C, the process pressure is 4Torr, the power is 10000W, and when depositing the back P-type doped microcrystalline silicon layer, PH3 is replaced by B2H6 gas, the flow rate of B2H6 is 100sccm, the CO2 flow rate is 25sccm, the volume ratio of B2H6 to SiH4 is 0.5 times, and the volume ratio of CO2 to SiH4 is 0.5 times; the remaining steps are the same.
[0123] Comparative Example 3
[0124] The preparation method of this comparative example is different from that of Example 1 in that: the doped amorphous silicon layer in step 4 is replaced by a doped microcrystalline silicon layer, and the specific steps are the same as those of depositing the second sub-doped microcrystalline silicon layer in Example 1; the remaining steps are the same.
[0125] Comparative Example 4
[0126] The preparation method of this comparative example is different from that of Example 1, except that: the front oxygen-doped amorphous silicon layer and the back oxygen-doped amorphous silicon layer deposited in step 3 are changed to the front intrinsic amorphous silicon layer and the back intrinsic amorphous silicon layer: specifically: SiH4 and H2 process gases are introduced, the SiH4 flow rate is 2000sccm, the H2 flow rate is 2000sccm, the ratio of H2 to SiH4 is 1.5, the chamber temperature is 200°C, the process pressure is 1.0Torr, and the power is 1000W; the remaining steps are the same.
[0127] Comparative Example 5
[0128] The preparation method of this comparative example is different from that of Example 1 in that the thickness of the first N-type sub-doped microcrystalline silicon layer on the front side and the first P-type sub-doped microcrystalline silicon layer on the back side deposited in step 4 are both 13 nm; the remaining steps are the same.
[0129] The batteries in Examples 1-12 and Comparative Examples 1-5 were tested under the same conditions. The test results are shown in Table 1.
[0130] Table 1 Test results of efficiency attenuation rate of cells in the examples and comparative examples under UV radiation
[0131]
[0132]
[0133] As can be seen from Table 1, from the comparison of the test data of Examples 1-12 and Comparative Examples 1-5, it can be seen that the scheme of the present invention can significantly reduce the efficiency attenuation rate under UV radiation.
[0134] From the comparison of the test data of Examples 1-9 and Examples 10-12, it can be seen that by using an oxygen-doped amorphous silicon layer, a doped amorphous silicon layer, and a first doped microcrystalline silicon layer under a protective gas atmosphere on the front and back of the battery, the efficiency attenuation rate of UV radiation is better.
[0135] From the comparison of the test data of the embodiment and comparative examples 1-3, it can be seen that by adopting the doped amorphous silicon layer and the concentration setting of the present invention, the efficiency attenuation rate under UV radiation can be significantly reduced.
[0136] From the comparison of the test data of the embodiment and the comparative example 4, it can be seen that by adopting the oxygen-doped amorphous silicon layer arrangement of the present invention, the efficiency attenuation rate under UV radiation can be significantly reduced.
[0137] From the comparison of the test data of the embodiment and the comparative example 5, it can be seen that by adopting the sub-doping layer thickness setting of the present invention, the efficiency attenuation rate under UV radiation can be significantly reduced.
[0138] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.
Claims
1. A heterojunction solar cell, characterized in that: include: A silicon substrate; the front side of the silicon substrate is provided with a front passivation layer, a front doping layer, a front transparent conductive layer, and a front metal electrode from the inside to the outside; The back side of the silicon substrate is provided with a back side passivation layer, a back side doping layer, a back side transparent conductive layer, and a back side metal electrode from the inside to the outside; Wherein, the front passivation layer and / or the back passivation layer comprises an oxygen-doped amorphous silicon layer; The front doped layer and / or the back doped layer comprises a doped amorphous silicon layer, wherein the hydrogen atom concentration of the doped amorphous silicon layer is 4.5×10 19 / cm 3 ~5.5×10 19 / cm 3 , the doping concentration of phosphorus or boron is 5.0×10 17 / cm 3 ~5.0×10 19 / cm 3 .
2. A heterojunction solar cell according to claim 1, characterized in that: The front doped layer and / or the back doped layer further include a doped microcrystalline silicon layer, the doped microcrystalline silicon layer is deposited on the front passivation layer and / or the back passivation layer, and the doped microcrystalline silicon layer includes at least two sub-doped microcrystalline silicon layers.
3. A heterojunction solar cell according to claim 2, characterized in that: The thickness of one layer of the sub-doped microcrystalline silicon layer is 15-25 nm.
4. The heterojunction solar cell according to claim 2, characterized in that: The doped microcrystalline silicon layer further includes a doped microcrystalline incubation layer. The doped microcrystalline incubation layer and the sub-doped microcrystalline silicon layer are deposited on the front passivation layer and / or the back passivation layer in a direction away from the silicon substrate.
5. The heterojunction solar cell according to claim 4, characterized in that: The thickness of the doped microcrystal incubation layer is 0.5-3 nm.
6. The heterojunction solar cell according to claim 4, characterized in that: The sub-doped microcrystalline silicon layer includes a first sub-doped microcrystalline silicon layer, and the first sub-doped microcrystalline silicon layer is deposited on the doped microcrystalline incubation layer; the first sub-doped microcrystalline silicon layer is formed in a protective gas atmosphere.
7. The heterojunction solar cell according to claim 1, characterized in that: The front passivation layer and / or the back passivation layer further includes at least one intrinsic amorphous silicon layer, and the intrinsic amorphous silicon layer is deposited on the oxygen-doped amorphous silicon layer.
8. The heterojunction solar cell according to claim 7, characterized in that: The thickness of the oxygen-doped amorphous silicon layer is smaller than that of the intrinsic amorphous silicon layer, and the thickness of the front passivation layer and / or the back passivation layer is 5-15 nm.
9. The heterojunction solar cell according to claim 1, characterized in that: The thickness of the front doping layer is 25-40 nm, and the thickness of the back doping layer is 30-45 nm; the thickness of the front doping layer is smaller than that of the back doping layer.
10. The heterojunction solar cell according to claim 1, characterized in that: The front doping layer is an N-type doping layer, and the back doping layer is a P-type doping layer.
11. The heterojunction solar cell according to claim 1, characterized in that: The material of the front transparent conductive layer and / or the back transparent conductive layer is at least one of AZO, ITO, IWO, FTO, and IOH, and has a thickness of 80 to 140 nm.
12. A method for preparing a heterojunction solar cell, characterized in that: The following steps are involved: Depositing an oxygen-doped amorphous silicon layer on the front side and / or the back side of the silicon substrate; Depositing a doped microcrystalline silicon layer and a doped amorphous silicon layer on the front passivation layer and / or the back passivation layer; The step of depositing doped amorphous silicon includes at least one of the following: Phosphorus source gas or boron source gas, silicon source gas and H2 are introduced into the chamber, wherein the volume ratio of phosphorus source gas to silicon source gas is 3.5 to 5.5 times, the volume ratio of boron source gas to silicon source gas is 1.5 to 3.5 times, the volume ratio of H2 to silicon source gas is 5 to 35 times, and the process pressure is 0.5 to 3 Torr.
13. A photovoltaic module, characterized in that: It comprises a heterojunction solar cell as described in any one of claims 1 to 11.